PENGEMBANGAN BAHAN AJAR BUMI DAN ANTARIKSA BERBASIS PEMBELAJARAN PROYEK DI PENDIDIKAN GURU SEKOLAH DASAR UNIVERSITAS NEGERI JAKARTA - A R Supriatna; Mitha Lyisa Angraini; Alvi Alfharizi; Mellinda Putri Astuti (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
The research method used is the method of research and development (Research and Development). The research and development method used in this study refers to the ADDIE development model. The stages that researchers must do to produce a product and test the effectiveness of the product include analysis, design stage, product manufacture, implementation and evaluation stage. The research was conducted in January-June 2023 at Jakarta State University Campus E which is at Jalan Setiabudi I number 1, South Jakarta as a validity test for product needs analysis and research determination to use teaching materials that have been designed. In this study the product development was PjBL (Project Based Learning) based teaching materials. The objectives to be achieved in this research include: 1) to develop project learning-based Earth and Space teaching materials to assist the learning process, 2) To test the feasibility of project-based Earth and Space teaching materials. 3) To identify the responses of Jakarta State University students to the attractiveness of the project-based Earth and Space teaching materials being developed. Research results and data obtained from the study, namely the feasibility of project-based earth and space teaching materials at Jakarta State University Elementary School Teacher Education according to the validation of the expert team, namely, from the two experts, an average percentage of 86.4% was obtained with very feasible criteria. / is very valid. The response of the Jakarta State University Elementary School Teacher Education students to project-based earth and space teaching materials at the Jakarta State University Elementary School Teacher Education is a percentage of 88.5% which is included in the very interesting category.